2020
DOI: 10.1177/0706743720904815
|View full text |Cite
|
Sign up to set email alerts
|

Influence of More Than 5 Years of Continuous Exposure to Antipsychotics on Cerebral Functional Connectivity of Chronic Schizophrenia

Abstract: Objective: To explore the effect of long-term antipsychotics use on the strength of functional connectivity (FC) in the brains of patients with chronic schizophrenia. Method: We collected resting-state functional magnetic resonance imaging from 15 patients with continuously treated chronic schizophrenia (TCS), 19 patients with minimally TCS (MTCS), and 20 healthy controls (HCs). Then, we evaluated and compared the whole-brain FC strength (FCS; including full-range, short-range, and long-range FCS) among patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…The difference in results may be associated with the heterogeneity of patients with schizophrenia. Nevertheless, research comprising functional or structural MRI using different analyses, such as global-brain FC ( Zhao et al, 2022 ), the dynamic amplitude of low-frequency fluctuation ( Wang et al, 2021 ), full- and short-range strength of FC ( Miao et al, 2020 ), and Trace ( Lee et al, 2016 ), have observed aberrant ITG in patients with schizophrenia, which is associated with psychotic ( Lee et al, 2016 ) and cognitive symptoms ( Lee et al, 2016 ) and might predict the response to an antipsychotic drug after 8 weeks ( Zhu et al, 2018 ). Previous studies also showed that both patients with schizophrenia and their unaffected siblings shared similar alterations in the ITG ( Liu H. et al, 2012 ; Zhu et al, 2018 ), and the neural activity of ITG was regulated by regulating by the Disrupted-in-Schizophrenia-1 gene ( Gou et al, 2018 ), suggesting that the ITG might be a potential biomarker of endophenotype for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in results may be associated with the heterogeneity of patients with schizophrenia. Nevertheless, research comprising functional or structural MRI using different analyses, such as global-brain FC ( Zhao et al, 2022 ), the dynamic amplitude of low-frequency fluctuation ( Wang et al, 2021 ), full- and short-range strength of FC ( Miao et al, 2020 ), and Trace ( Lee et al, 2016 ), have observed aberrant ITG in patients with schizophrenia, which is associated with psychotic ( Lee et al, 2016 ) and cognitive symptoms ( Lee et al, 2016 ) and might predict the response to an antipsychotic drug after 8 weeks ( Zhu et al, 2018 ). Previous studies also showed that both patients with schizophrenia and their unaffected siblings shared similar alterations in the ITG ( Liu H. et al, 2012 ; Zhu et al, 2018 ), and the neural activity of ITG was regulated by regulating by the Disrupted-in-Schizophrenia-1 gene ( Gou et al, 2018 ), suggesting that the ITG might be a potential biomarker of endophenotype for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“… Zhu et al (2020) stated that the right ITG might show unique abnormalities in patients with schizophrenia compared with those with bipolar disorder and attention-deficit/hyperactivity disorder. Moreover, Miao et al (2020) showed that the functional impairment in this region might be an ongoing pathological process in schizophrenia patients, and it is barely affected by antipsychotic drugs. Above all, to a certain extent, our results provided diverse findings regarding ITG and novel insights into exploring symptomatic and cognitive-related mechanisms in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy identified 459 studies, and 21 of them met our inclusion criteria 10 16 , 52 65 , comprising a total of 1057 patients with schizophrenia (mean age: 26.1) and 1186 healthy controls (mean age: 27.5). Four of the included studies divided patients with schizophrenia into two subgroups according to clinical characteristics 52 , 53 , 55 , 61 , and thus the two sets of data were obtained from each study. The diagnostic criteria employed in the literature included in our study were predominantly based on widely recognized and accepted classifications, including the Diagnostic and Statistical Manual of Mental Disorders (DSM) and the International Classification of Diseases (ICD).…”
Section: Resultsmentioning
confidence: 99%